RELASI PENCEGAHAN STUNTING DAN UPAYA MEWUJUDKAN KELUARGA SAKINAH (Studi Kasus Di Balai Penyuluh Keluarga Berencana (Kb) Kecamatan Mojotengah) - Anggun Indriyani; Mutho’am Mutho’am (Hukum Keluarga Islam, 2022)
One of the goals of marriage is to create good and quality offspring. In this case, the readiness of the parties is a necessity, including in efforts to prevent the birth of stunting toddlers. The birth of a stunted toddler has a negative impact both on the toddler, such as the child's health condition which is prone to disease, the child's low intelligence and the impact on his family such as the prolonged cycle of poverty. This study itself aims to find out the steps to prevent stunting in Slukatan Village by the Family Planning Extension Center (KB) of the Mojotengah District and its relation to efforts to create a sakinah family. This field research uses qualitative methods. The data obtained is through observation, interviews, and documentation. After the data is collected, it is then described and concluded in an inductive way. The results of this study indicate that the prevention of stunting in Slukatan Village by the Family Planning Counselor Center for Family Planning in the District of Mojotengah is carried out incidentally and is carried out in 3 stages, namely the awareness stage, the skills proficiency stage, the intellectual development stage. Efforts to prevent stunting, such as coaching prospective brides, assisting pregnant women, activities understanding 1000 HPK nutrition and providing complementary foods related to providing halal and thayyib food for children, and implementing a healthy lifestyle are related to creating a sakinah family that idealizes peace and comfort in a family connection.